La transmission des savoir-faire dans les ateliers de costumes et de l’habillement de la Comédie-Française - Agathe Sanjuan (In Situ)
How is it possible to study the history of the gestures of theatrical costume professionals? At first view, the question seems to be quite a challenge. Nonetheless, it is possible to retrace some of the fragments of this story through the archives of the Comédie-Française, if only by looking at the large number of trades involved in dressing actors for the stage. And today the costume workshops of the Comédie-Française still generate archives which are carefully preserved by the theatre’s library-museum. But to get even closer to the reality of this transmission of skills, nothing beats the oral testimony of a professional involved. The present article results from the exceptional example of a double interview, first of Renato Bianchi, a tailor recruited by the Comédie-Française in 1964 and who went on to become head tailor and then director of the theatre’s costume services up to 2012, and then of Sylvie Lombart, an independent costume designer and Bianchi’s collaborator, and who succeeded him in his job as director. The interview covers fifty years of the tradition of the ‘belle main’, the skilled hand: how to sew, how to cut, how to design a costume and even questions such as how to hold a thimble or the song of the needle…